Impact of macro economic factors and financial development on energy projects - case in ASEAN countries - Hanh Hoang Thanh; Huy Dinh Tran Ngoc; Phuong Nguyen Thi Thanh; Nga Le Thi Viet; Anh Pham Tuan (Zielona Góra: Faculty of Economics and Management Press)
ASEAN (The Association of SouthEast Asian Nations) demand on energy is depending on economic growth of each country, resources, and political and regulations of each country. This study aims to investigate the role of international trade, financial development, foreign direct investment (FDI) on the consumption of renewable energy (RE) in ASEAN countries of the world.
Keywords: countries ASEAN; commerce; financial development; energy project; macroeconomic; macro politicies; kraje ASEAN; handel; rozwój finansowy; projekty energetyczne; makroekonomia; makropolityka